(3GdHjGf aj abg GdgOhjIs - (3eYhVIs
(3ChdgG (B:s
(3Ghdg eHJhQ , hjHOC GdehLhO efg CKfGA HGH GdhVhA , Hbhdg (B: (3de jLR Pdc GdhVhA dZQV hdG fad , aEf CQGO GdQLhY Edi eG UQag Yfg hLH Ydjg Cf jCJi HGdhVhA , ef MjK ZjQ GdfjI s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi ai ChGFd cJGH GdfabGJ s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJ hHYV GdTQhMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3abg GdgOhjI (B93) s
Keywords: (3abg GdePGgH GdCNQis